Suomen työeläkejärjestelmän stokastinen kedtävyysanalyysi - Jukka Lassila; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2008)
This study analyzes the sustainability implications of demographic and investment risks in the Finnish private sector pension system (TyEL). The results show that current contribution rate is likely to be too low to finance the future higher expenditure. The main sustainability problem is not, however, the generally projected increase in the contribution rate, but the outstanding probability of the contribution being much higher than expected in the long term. A recent reform aimed at lowering the expected increase in the contribution rate by increasing the share of stocks in the portfolios of the pension funds. It is likely to do so, unless the increased risk causes unforeseen changes to the pension system, with sustainability implications that may outweigh the expected gains from better asset yields. A long-lasting solution to the sustainability problem could be the adoption of a Swedish type NDC pension system. Our simulations show, however, that the implied adjustment rules may not react early enough to the realized demographic or investment risks, and therefore risk sharing between generations would not be sufficient. Future research should study adjustment mechanisms that restrict the probability of large hikes in the contribution rate without fixing the contribution rate permanently.
Keywords: H55; J11; 330; Sustainability; demographic risks; investment risks; pension funds; Alterssicherung; Pensionsfonds; Rentenfinanzierung; Bevölkerungsentwicklung; Finnland